Interleukin 9 mediates T follicular helper cell activation to promote antibody responses - Sato, Taiki; Ikegami, Ippei; Yanagi, Masahiro; Ohyu, Takeshi; Sugaya, Taiki; Shirato, Shotaro; Tanemoto, Masanobu; Kamiya, Shiori; Kikuchi, Kohei; Kamada, Yuka; Nakata, Takehito; Kamekura, Ryuta; et al. (Frontiers in Immunology, 2024)
Antigen-specific humoral responses are orchestrated through complex interactions among immune cells in lymphoid tissues, including the collaboration between B cells and T follicular helper (Tfh) cells. Accumulating evidence indicates a crucial role for interleukin-9 (IL-9) in the formation of germinal centers (GCs), enhancing the generation of class-switched high-affinity antibodies. However, the exact function of IL-9 in Tfh cell regulation remains unclear. In this study, we examined the humoral immune responses of CD4 Cre/+ Il9ra fl/fl mice, which lack an IL-9-specific receptor in Tfh cells. Upon intraperitoneal immunization with sheep red blood cells (SRBCs), CD4 Cre/+ Il9ra fl/fl mice displayed diminished levels of SRBC-specific IgG antibodies in their sera, along with reduced levels of GC B cells and plasma cells. Notably, Il9ra-deficient Tfh cells in the spleen exhibited decreased expression of their signature molecules such as B-cell lymphoma 6, C-X-C chemokine receptor 5, IL-4, and IL-21 compared to control mice. In models of allergic asthma induced by house dust mite (HDM) inhalation, CD4 Cre/+ Il9ra fl/fl mice failed to elevate serum levels of HDM-specific IgE and IgG. This was accompanied by reductions in Tfh cells, GC B cells, and plasma cells in mediastinal lymph nodes. Furthermore, group 2 innate lymphoid cells (ILC2s) were identified as producers of IL-9 under immunizing conditions, possibly induced by leukotrienes released by activated IgD + B cells around the T-B border. These observations may indicate the critical role of IL-9 receptor signaling in the activation of Tfh cells, with ILC2s potentially capable of supplying IL-9 in organized lymphoid tissues.